2016
DOI: 10.1111/dme.13162
|View full text |Cite
|
Sign up to set email alerts
|

An empirically derived short form of the Hypoglycaemia Fear Survey II

Abstract: The short form of the Hypoglycaemia Fear Survey II is an important first step in more efficiently measuring fear of hypoglycaemia. Future prospective studies are needed for further validity testing and exploring the survey's applicability to different populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Higher scores indicate greater fear of hypoglycaemia. 28 Adequate Cronbach's α values have been reported for the avoidance subscale (0.76), maintain high subscale (0.83), worry subscale (0.78) and total scale (0.83). 28 …”
Section: Methodsmentioning
confidence: 98%
“…Higher scores indicate greater fear of hypoglycaemia. 28 Adequate Cronbach's α values have been reported for the avoidance subscale (0.76), maintain high subscale (0.83), worry subscale (0.78) and total scale (0.83). 28 …”
Section: Methodsmentioning
confidence: 98%
“…Additionally, incorporating fear of hypoglycemia surveys and recent studies identifying predictors of hypoglycemia would also be clinically useful and relevant. 8182 This will help to provide clinicians with an updated and more precise portrait of the long-term effects of hypoglycemia and contemporary intensive glycemic control.…”
Section: Expert Commentarymentioning
confidence: 99%
“…However, the scale not only has many entries, but also lacks clear cutoff value. Moreover, a research found that the internal equity of the behavior subscale is low and has no subjective interpretation related to behavior [[9], [10], [11]]. To this end, Anarte et al.…”
Section: Introductionmentioning
confidence: 99%